Pengaruh Elemen Teori Fraud Hexagon Terhadap Financial Statement Fraud pada BUMN di BEI - Albert Andhika Endratama; Tutut Dewi Astuti (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The purpose of this study is to examine the hypothesis that fraudulent financial reporting is impacted by the six factors of the fraud hexagon theory (pressure, opportunity, rationalization, capacity, ego, and cooperation). Financial security and outside pressure stand in for the stress factor. Opportunity is represented by inefficient management. Changing auditing firms stands in for the justification factor. The capacity element is represented by a change in directors. The abundance of CEO portraits in the financial reports represents the ego aspect, while the prevalence of multi-hatted board commissioners represents the cooperation factor. This study uses a sample size of 120 data from State-Owned Enterprises registered on the BEI between 2018 and 2022 as its population. Purposive sampling was used in the data collection process. Descriptive statistics, logistic regression analysis, the overall model fit test, the test for the coefficient of determination, the test for the feasibility of the regression model, the classification matrix test, and the regression coefficient test are all used. According to these findings, financial stability can reduce the likelihood of fraud in financial reporting, as indicated by a significance value smaller than 0.05, namely 0.015. Meanwhile, ineffective supervision and auditor turnover increase the likelihood of fraud in financial reporting, with significance values of 0.030 and 0.000, respectively. On the other hand, external pressure, director turnover, arrogance, and collusion do not significantly influence the prevalence of fraud in financial reporting, with significance values greater than 0.05, namely 0.354, 0.066, 0.100, and 0.104, respectively.